Weekly Intramuscular Injection of Levothyroxine following Myxoedema: A Practical Solution to an Old Crisis - Peter N. Taylor; Arshiya Tabasum; Gina Sanki; David Burberry; Brian P. Tennant; James White; Onyebuchi Okosieme; Andrew Aldridge; Gautam Das (Case Reports in Endocrinology)
An 82-year-old female with known hypothyroidism was admitted to hospital after being found on the floor. On examination, she was unkempt, confused, bradycardic, hypothermic, and barely arousable. Initial biochemistry revealed a thyroid stimulating hormone (TSH) of >100 mU/L and free thyroxine (FT4) level of 1.5 pmol/L which supported a diagnosis of myxoedema coma. She was resuscitated and commenced on liothyronine, levothyroxine, and hydrocortisone and some improvement was made. It became apparent that she was hiding and spitting out her oral levothyroxine including levothyroxine elixir. Given the need for prompt alternative control, we sought advice from international experts where intramuscular levothyroxine was recommended. She was managed from day 50 onwards with intramuscular levothyroxine 200 mcg once a week, which was subsequently increased to 500 mcg. Thyroid function normalized and she made continual cognitive and physical progress and was discharged to a rehabilitation hospital. Her intramuscular levothyroxine was stopped and she was subsequently restarted on oral levothyroxine, with a plan for on-going close monitoring of her thyroid function. This report highlights the potential to use intramuscular levothyroxine in individuals with severe hypothyroidism arising from poor compliance with levothyroxine treatment or other potential causes such as impaired absorption.